Model for bidirectional movement of cytoplasmic dynein. (7th September 2015) - Sumathy, S.; Satyanarayana, S.V.M.
Abstract: Cytoplasmic dynein exhibits a directional processive movement on microtubule filaments and is known to move in steps of varying length based on the number of ATP molecules bound to it and the load that it carries. It is experimentally observed that dynein takes occasional backward steps and the frequency of such backward steps increases as the load approaches the stall force. Using a stochastic process model, we investigate the bidirectional movement of single head of a dynein motor. The probability for backward step is implemented based on fluctuation theorem of non-equilibrium statistical mechanics. We find that the movement of dynein motor is characterized with negative velocity implying backward motion beyond stall force. We observe that the motor moves backward for super stall forces by hydrolyzing the ATP exactly the same way as it does while moving forward for sub-stall forces. Movement of dynein is also simulated using a kinetic Monte Carlo method and the simulated velocities are in good agreement with velocities obtained using a stochastic rate equation model. Abstract : Highlights: Stochastic process models are developed for bidirectional motion of dynein motor. Probability for backward step uses Crook׳s like fluctuation theorem. Average motor velocity is negative beyond stall force. Backward motion beyond stall force is also powered by ATP hydrolysis.